Environmental risk factors, protective factors, and biomarkers for amyotrophic lateral sclerosis: an umbrella review - Qian Wu; Junyi Yang; Yuanjie Duan; Yumei Ma; Yue Zhang; Shutong Tan; Jinke Wang; Yaxin Wang; Binhui Liu; Jian Zhang; Jian Zhang; Xu Liu; et al. (Frontiers in Aging Neuroscience)
IntroductionAmyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by the rapid loss of motor neurons. Given the significant global economic impact of ALS, effective preventive measures are urgently needed to reduce the incidence of this devastating disease. Recent meta-analyses have explored potential links between environmental factors, biomarkers, and ALS occurrence. However, the findings of these studies have been inconsistent and controversial. Therefore, we present a comprehensive umbrella review of recent meta-analyses to systematically summarize the available epidemiological evidence and evaluate its credibility.MethodsA systematic search was conducted in PubMed and Embase from inception until 01 October 2024, to identify meta-analyses of observational studies examining associations between environmental risk factors, protective factors, biomarkers, and ALS susceptibility. For each meta-analysis, summary effect estimates, 95% confidence intervals (CIs), 95% prediction intervals, study heterogeneity, small study effects, and excess significance biases were calculated independently by two investigators. The methodological quality was evaluated using the AMSTAR 2 criteria. The strength of the epidemiological evidence was categorized into five levels based on predefined criteria.ResultsOut of 1,902 articles identified, 43 met the inclusion criteria, resulting in 103 included meta-analyses. These analyses covered 46 environmental risk and protective factors (344,597 cases, 71,415,574 population) and 57 cerebrospinal fluid (CSF) and serum biomarkers (30,941 cases, 2,180,797 population). The evidence was classified as convincing (Class I) for the regular use of antihypertensive drugs (OR: 0.85, 95% CI: 0.81–0.88) and highly suggestive (Class II) for premorbid body mass index (OR: 0.97, 95% CI: 0.95 to 0.98), trauma (OR: 1.51, 95% CI: 1.32 to 1.73), CSF NFL levels (SMD: 2.06, 95% CI: 1.61 to 2.51), serum NFL levels (SMD: 1.57, 95% CI: 1.29 to 1.85), ferritin levels (SMD: 0.66, 95% CI: 0.50 to 0.83), and uric acid levels (SMD: −0.72; 95% CI: −0.98 to −0.46).DiscussionThis umbrella review offers new insights into the epidemiological evidence regarding the associations between environmental factors, biomarkers, and ALS susceptibility. We aim for our study to enhance the understanding of the roles of environmental factors and biomarkers in ALS occurrence and assist clinicians in developing evidence-based prevention and control strategies.